Mechanical and Biocompatibility Properties of Calcium Phosphate Bioceramics Derived from Salmon Fish Bone Wastes - Bas, Merve; Daglilar, Sibel; Kuskonmaz, Nilgun; Kalkandelen, Cevriye; Erdemir, Gokce; Kuruca, Serap E.; Tulyaganov, Dilshat; Yoshioka, Tomohiko; Gunduz, Oguzhan; Ficai, Denisa; Ficai, Anton (MDPI, 2020)
Natural calcium phosphates derived from fish wastes are a promising material for biomedical application. However, their sintered ceramics are not fully characterized in terms of mechanical and biological properties. In this study, natural calcium phosphate was synthesized through a thermal calcination process from salmon fish bone wastes. The salmon-derived calcium phosphates (sCaP) were sintered at different temperatures to obtain natural calcium phosphate bioceramics and then were investigated in terms of their microstructure, mechanical properties and biocompatibility. In particular, this work is concerned with the effects of grain size on the relative density and microhardness of the sCaP bioceramics. Ca/P ratio of the sintered sCaP ranged from 1.73 to 1.52 when the sintering temperature was raised from 1000 to 1300 degrees C. The crystal phase of all the sCaP bioceramics obtained was biphasic and composed of hydroxyapatite (HA) and tricalcium phosphate (TCP). The density and microhardness of the sCaP bioceramics increased in the temperature interval 1000-1100 degrees C, while at temperatures higher than 1100 degrees C, these properties were not significantly altered. The highest compressive strength of 116 MPa was recorded for the samples sintered at 1100 degrees C. In vitro biocompatibility was also examined in the behavior of osteosarcoma (Saos-2) cells, indicating that the sCaP bioceramics had no cytotoxicity effect. Salmon-derived biphasic calcium phosphates (BCP) have the potential to contribute to the development of bone substituted materials.
Keywords: salmon fish bone; hydroxyapatite; mechanical properties; sintering; HYDROXYAPATITE COMPOSITES; Biochemistry & Molecular Biology; Chemistry